MONETARY AND FISCAL POLICY ANALYSIS: WHICH IS MORE EFFECTIVE? - Muhamad Yunanto; Henny Medyawati (Journal of Indonesian Economy and Business (JIEB), 2014)
Fiscal policy is an adjustment in the income and expenditure of government as stipulated in the state budget in order to achieve better economic stability and pace of development. The main objective of this study was to measure and analyze Fiscal and Monetary Policy of the Gross Domestic Product (GDP). Fiscal Policy Multiplier (FPM) and Monetary Policy Multiplier (MPM) are used to answer the debate where more effective between fiscal policy and monetary policy. Short-term models derived through error correction model (ECM), which also forms the derivative equation. A system of simultaneous equations two stage least squares (TSLS), is used to describe the sensitivity analysis (response) of shocks to the policy change of important macroeconomic indicators. The results showed that during the study period, Indonesia's monetary policy more effective than fiscal policy.